Leveraging Social Media Data for Sustainable Tourism Development: Spatial Analysis of Tourist Destinations - Widarmanti, Tri; Ramantoko, Gadang; Rifaldi Windya Giri , Refi (Journal of Tourism Sustainability, 2024)
The COVID-19 pandemic significantly disrupted the tourism industry by restricting social activities and raising concerns about overcrowding at popular destinations. To address these challenges, effective strategies are needed to manage visitor distribution. This study analyzes social media data from a travel platform, including reviews and ratings, to assess the distribution and popularity of tourist destinations in West Java. The research explores the potential of social media as a resource for local tourism planning and development, aiming to enhance West Java's rich offerings in arts, culture, culinary experiences, and adventure tourism. Findings reveal visitor patterns, with a concentration of tourists in urban areas compared to districts, and highlight the popularity of natural attractions in Bogor, Sukabumi, Bandung, Garut, and Pangandaran. Additionally, Cirebon emerges as a key hub for cultural tourism and transit. By leveraging reviews and spatial data, this study underscores the role of social media in supporting sustainable tourism strategies. Tools like ArcGIS are recommended to visualize tourist patterns, promote ecotourism, and achieve West Java's green tourism goals in the post-pandemic era.